PERAWATAN PROSTHODONTIK PADA KONDISI RIDGE YANG KURANG MENGUNTUNGKAN - Susi R. Puspitadewi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
Extreme resorption of the maxillary and mandibular denture bearing areas results in sunken appearance of cheeks, unstable and non retentive denture with associated pain and discomfort. Prosthodontic rehabilitation of a patient with compromised edentulous ridges in a conventional manner is a difficult task. Modifications in the treatment procedures should be considered to fulfil the patient's functional and esthetic desires. This article reviews the various compromised situations commonly encountered in a routine clinical practice and the possible management of each of them.